The hive--book 2 of the second formic war eaudiobook The second formic war series, book 2. - Card, Orson Scott (The Second Formic War, 2019)
New York Times bestselling authors Orson Scott Card and Aaron Johnston return to the prequels to Ender's Game following The Swarm with The Hive , the second audiobook in the Second Formic War. Card and Johnston continue the fast-paced hard science fiction history of the Formic Wars—the alien invasions of Earth's Solar System that ultimately led to Ender Wiggin's total victory in Ender's Game . A coalition of Earth's nations barely fought off the Formics' first scout ship. Now it's clear that there's a mother-ship out on the edge of the system, and the aliens are prepared to take Earth by force. Can Earth's warring nations and corporations put aside their differences and mount an effective defense? Ender's Game is one of the most popular and bestselling science fiction titles of all time. The Formic War series (The First Formic War and The Second Formic War) are the prequels to Ender's story. THE ENDER UNIVERSE: Ender series Ender's Game / Speaker for the Dead / Xenocide / Children of the Mind / Ender in Exile / Children of the Fleet Ender's Shadow series Ender's Shadow / Shadow of the Hegemon / Shadow Puppets / Shadow of the Giant / Shadows in Flight The First Formic War (with Aaron Johnston) Earth Unaware / Earth Afire / Earth Awakens The Second Formic War (with Aaron Johnston) The Swarm / The Hive Ender novellas A War of Gifts / First Meetings This program is read by Orson Scott Card, Vikas Adam, Paul Boehmer, Susan Hanfield, Arthur Morey, Emily Rankin, Stefan Rudnicki, Rob Dean, and Gabrielle de Cuir.